The improvement of collaborative learning through the digital storytelling tasks (Global Scientific Review, 2023)
The purpose of the following article is to demonstrate the effectiveness of digital storytelling tasks in EFL classes. Digital storytelling tasks can be useful instruments to enhance learners’ interest toward to lesson process and at the same time improve collaboration as well as creativity in English classrooms. The usage of digital storytelling tasks aid educators to attain better results in their lessons. This work also shows that digital storytelling activity has positive effect on the interaction process among learners.